2010
DOI: 10.1155/2010/757908
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIF-1 and HIF2 on Growth and Metabolism of Clear-Cell Renal Cell Carcinoma 786-0 Xenografts

Abstract: In cultured clear-cell renal carcinoma (CCRCC) 786-0 cells transfected with HIF1α (HIF-1+), HIF-2α (HIF-2+), or empty vector (EV), no significant differences were observed in the growth rates in vitro, but when grown in vivo as xenografts HIF-2α significantly increased, and HIF-1α significantly decreased growth rates, compared to EV tumors. Factors associated with proliferation were increased and factors associated with cell death were decreased in HIF-2+ tumors. Metabolite profiles showed higher glucose and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 46 publications
6
61
0
1
Order By: Relevance
“…5C). Despite some overlapping effects, it has been reported that HIF-1␣ and HIF-2␣ regulate distinct genes (7,32). For example, HIF-1␣ is primarily involved in glucose metabolism, including upregulation of glycolytic enzymes and downregulation of electron transport chain activity (7).…”
Section: Discussionmentioning
confidence: 99%
“…5C). Despite some overlapping effects, it has been reported that HIF-1␣ and HIF-2␣ regulate distinct genes (7,32). For example, HIF-1␣ is primarily involved in glucose metabolism, including upregulation of glycolytic enzymes and downregulation of electron transport chain activity (7).…”
Section: Discussionmentioning
confidence: 99%
“…30 Interestingly, HIF2α-xenografts demonstrate elevated expression of key mitochondrial proteins, such as pyruvate dehydrogenase (PDH, catalyzing the first step of the Krebs cycle) and TOMM20, the decreased expression of the Krebs cycle inhibitor pyruvate dehydrogenase kinase (PDK1), and decreased intra-tumoral lactate levels, indicating that HIF2α-tumors rely less on glycolysis and more on oxidative metabolism. 30 Conversely, HIF1α-xenografts demonstrated elevated expression of PDK1 and the mitophagy marker BNIP3, suggesting that HIF1α in renal cancer cells functions as a tumor suppressor and promotes autophagic cell death. 30 HIF2α in epithelial cancer cells plays an important role in the pathogenesis and prognosis of some type of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…VHL encodes an E3 ubiquitin ligase ( 12,13 ) that targets HIF1α ( HIF1A ) and HIF2α ( EPAS1 ) for degradation ( 14,15 ). VHL loss in ccRCC results in constitutive activation of HIF1/2α and subsequent transactivation ( 16,17 ) of downstream genes regulating angiogenesis, glycolysis ( 18 ), lipogenesis ( 19,20 ), cell cycle ( 21 ), and antiapoptosis ( 22 ).…”
mentioning
confidence: 99%